Román Aleny Vostré - Všetička, František (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2014)
Alena Vostrá built her first novel Lukewarm Wave (1966) on the catenal principle and the principle of a game. Its structure consists to a large extent of variational and framing chapters. The tectonics of Lukewarm Wave has a number of similarities with the picaresque novel, with the main work of J. Hašek and the initial novels of L. Fuks.
Keywords: Catenal principle, principle of a game, variational chapters, framing chapters, J. Hašek, L. Fuks